POLITIK HUKUM UNDANG-UNDANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Astuti, Indri (Forum Ilmu Sosial, 2014)
Political law is very interesting to be learnt because of the political law describes how the changes to be made in the applicable law in order to meet the needs of the community, to discuss the process off ormation of is constitutumius constituendumin the face of changes in people's lives, as wellas legal changes resulting product which sets the frame work and direction of development law. As reviewed in this article include: (1) How does them history of the development of legislation to era dicate corruption in Indonesia, and (2) How is the political assessment of the law against the law to eradicate corruption in the development of legislation Indonesia. Thehistory of corruption begins with the background to the rules of military ruler on April 9, 1957. The Eradication corruption. In reformation era the subtitute of legislation of the new ordere merging Act No. 31 of 1999 which then under goes refinement by Act No. 20 of 2001. political Studies Law Law corruption eradication in terms of philosophical, pragmatic and sosiologis. To provide legal political analysis, the writer tries to give input on the final legislation that Act No. 20 of 2001 to see a few things to note is about the ruleson the subject of qualify in goffense, not minimal criminal implementation guide lines specifically, the absence of specific provisions regarding the implementation of the criminal fines are not paid by the corporation, the absence of specific provisions that define the notion of the termof agreementevil, the transition rule in Article 43 A of Law No. 20 of2001 which was conside redexcessive, Dead Criminal formulation which is only valid for one article, namely Article 2 paragraph (1) as well ason Recidive.